Utilization of social networking sites by small home-based business - Percol, Dianne Kamille L.; Chua, Consuelo T. (2010.)
ABSTRACT This study examined the use of social networking sites (SNSs) by small home-based enterprises. Specifically, it described the business functions wherein social networking sites are utilized; and analyzed the strengths, opportunities, weaknesses and threats of utilizing SNSs for business operations.
Twenty home-based entrepreneurs, who use SNS for their businesses, were purposively chosen to participate in the study. The survey method was utilized to determine the nature and characteristics of the businesses; while personal interview was used to analyze the strengths, weaknesses, opportunities, and threats of utilizing SNS. Data was analyzed using descriptive statistics and content analysis.
Results show that most of the home-based businesses in this study are new, and have been operating for less than two years. All of the businesses have asset sizes of less that PhP 1.5 Million, most of which are managed and owned by sole proprietors. These businesses mainly cater to local clients, although some of them also target international customers. In general, the target market of the businesses comprises middle income male and female customers, especially those under the teenage and young adult age groups.
The home-based enterprises utilize social networking sites mainly for advertising and promoting their products and services. Other business functions wherein SNSs are used include online cataloguing of products, transaction of sales, and market research. The main strength of using SNSs for the businesses involve cost and time saving benefits; followed by easy access to business information and convenience of use. On the other hand, the weaknesses that were identified include technical disadvantages, the lack of physical products, and difficulty in gaining customer trust and loyalty. Wider market reach and publicity were recognized as the opportunities; while the presence of fake clients and competition within and outside the Web, were identified as threats.
Recommendations for researchers, home economists, educators and students are provided at the end of the paper.
Thesis (B.S. Home Economis)--University of the Philippines Diliman.
Keywords: Online social networks; Electronic commerce